The New Antibacterial Properties of the Plants: Quo vadis Studies of Anti-virulence Phytochemicals? - Díaz-Nuñez, José Luis; García-Contreras, Rodolfo; Castillo-Juárez, Israel (Frontiers in Microbiology, 2021)
In recent years, the increase in bacterial resistance to antibiotics has favored the resurgence of the study of natural antimicrobial products. For centuries, plants have been recognized for their bactericidal properties; however, in the last two decades, it has been reported that several plants derived metabolites at growth subinhibitory concentrations also tend to have anti-virulence properties, since they reduce the expression of virulence factors that cause damage and the establishment of pathogenic bacteria. In this area of study, plants have positioned themselves as one of the main natural sources of anti-virulence molecules; however, only a small portion of the plant species that exist has been investigated and the antivirulence studies had been primarily aimed at analyzing the ability of extracts and compounds to inhibit quorum sensing and biofilms using in vitro assays. This mini-review discusses the current panorama, the trends in the study of anti-virulence phytochemicals, as well as their potential for the development of antibacterial therapies.